Origin and age of the causative mutations in KLC2, IMPA1, MED25 and WNT7A unravelled through Brazilian admixed populations - Allysson Allan de Farias (Nature Portfolio, 2018)
Abstract The mutation age and local ancestry of chromosomal segments harbouring mutations associated with autosomal recessive (AR) disorders in Brazilian admixed populations remain unknown; additionally, inbreeding levels for these affected individuals continue to be estimated based on genealogical information. Here, we calculated inbreeding levels using a runs of homozygosity approach, mutation age and local ancestry to infer the origin of each chromosomal segments containing disorder-causing mutations in KLC2, IMPA1, MED25 and WNT7A. Genotyped data were generated from 18 patients affected by AR diseases and combined to the 1000 genome project (1KGP) and Simons genome diversity project (SGDP) databases to infer local ancestry. We found a major European contribution for mutated haplotypes with recent mutation age and inbreeding values found only in Native American and Middle East individuals. These results contribute to identifying the origin of and to understanding how these diseases are maintained and spread in Brazilian and world populations.